1999
DOI: 10.1038/sj.bjc.6690228
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and therapeutic approaches for nonmetastatic breast cancer in Canada, and their associated costs

Abstract: In an era of fiscal restraint, it is important to evaluate the resources required to diagnose and treat serious illnesses. As breast cancer is the major malignancy affecting Canadian women, Statistics Canada has analysed the resources required to manage this disease in Canada, and the associated costs. Here we report the cost of initial diagnosis and treatment of nonmetastatic breast cancer, including adjuvant therapies. Treatment algorithms for Stages I, II, and III of the disease were derived by age group (<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…Although there is a growing literature on the economics of cancer care, it has largely focused on the increasing proportion of global health spending accounted for by cancer care. [18][19][20][21] Little attention has been paid to the economic consequences of cancer among survivors and their families. We found that patients who were treated solely with the more expensive AI drugs were more likely to experience financial difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is a growing literature on the economics of cancer care, it has largely focused on the increasing proportion of global health spending accounted for by cancer care. [18][19][20][21] Little attention has been paid to the economic consequences of cancer among survivors and their families. We found that patients who were treated solely with the more expensive AI drugs were more likely to experience financial difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…In the early 1990s, Statistics Canada developed the Population Health Model to "assist in the evaluation of cancer control interventions and policy decision-making" 1 , with a focus on lung 2,3 , breast [4][5][6] , and colorectal cancers 7 . More recently, the Canadian Partnership Against Cancer developed the Cancer Risk Management Model to "gain insight into the cost/benefit of cancer control strategies to help guide and strengthen decision-making" 8 , with a focus on lung 9 and colorectal cancers 10 .…”
Section: Introductionmentioning
confidence: 99%
“…The greatest economic burden was observed among patients who had distant recurrences, adding to previous findings that patients with advanced breast cancer at diagnosis incur significantly more healthcare charges compared with patients who are diagnosed at an earlier stage. [3][4][5][6][7] Furthermore, for all recurrence types (i.e., locoregional, contralateral breast, and distant recurrences), postrecurrence charges for care were significantly greater than prerecurrence charges. These results are consistent with a previous study in men with prostate cancer in which it was noted that metastatic progression and prostate-specific antigen progression were associated with significantly greater healthcare charges compared with patients who did not have disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…ies that evaluated the cost of breast cancer care, [3][4][5][6][7] but none of those authors investigated the economic burden associated with disease recurrence among women with early breast cancer. This represents an important gap in current knowledge for physicians and payors alike, because such information may help to quantify the benefit of recommended new (and generally more expensive) treatments that significantly reduce the risk of breast cancer recurrence.…”
mentioning
confidence: 99%